Influence of Sustainable Agricultural Practices on Ecosystem Balance and Land Productivity in Indonesia - Muhammad Hazmi; Rosa Zulfikhar; Fitriah Suryani Jamin; Magdalena Sunarty Pareira; Slamet Pamuji (West Science Agro, 2024)
This research investigates the influence of sustainable agricultural practices on ecosystem balance and land productivity in Indonesia through a mixed-methods approach. A sample of 500 farmers across diverse regions participated in surveys and field measurements, contributing to a comprehensive analysis. The study reveals varying adoption rates of sustainable practices, with organic farming and agroforestry emerging as prominent choices. Statistical analysis using Structural Equation Modeling with Partial Least Squares (SEM-PLS) demonstrates significant positive relationships between sustainable practices and ecosystem indicators, including biodiversity, soil health, and crop yields. Regional variations highlight the context-specific nature of these practices. The findings carry implications for policy formulation, extension services, and the promotion of sustainable agriculture in Indonesia.